Pemanfaatan Podcast sebagai Media Dakwah di Era Digital - Erwan Efendi; Mhd. Habib Ansyahri Siregar; Dila Popyanti; M Ridwan (VISA: Journal of Vision and Ideas, 2024)
Podcasts are one of the many social media platforms that are growing rapidly. According to Fadilah (2017), podcasts are defined as online audio or video content that can be downloaded automatically to computers and smartphones for free or by subscription. This podcast content is a news source for internet-based radio broadcasts. The success of using podcast media for preaching can be seen from Ali Jaber and Habib Husain Jaffar Al Hadar. This research is descriptive qualitative research. The data source was obtained from searches of various podcast service provider sites and several previously existing related studies. Data was collected using documentation techniques and analyzed using the Huberman and Miles concept, namely through data reduction, data presentation, and drawing conclusions and verification. In 2005, podcasts began to gain popularity in Indonesia. On his weblog, Boy Avianto created his first podcast entitled "Any Podcast". Three years later, Soundcloud, an easier-to-use podcast creation and listening platform, was introduced. Podcasts have their own advantages in terms of communication and information because they are a medium that is currently continuing to develop to meet the needs of its audience. This can provide an opportunity for preachers to broadcast their da'wah using podcasts as a platform. Utilization of Podcasts as a Da'wah Media As a medium that is currently experiencing development in pampering its audience, podcasts also have their own advantages both in communication and information. One proof of the use of podcasts as a medium for da'wah is the many positive comments made by netizens, how they really enjoy and feel the preaching carried out by Habib Ja'far, even though from afar, one of the positive comments made is from the account @qyubayakustik9166 "We really grateful to be able to know Habib Ja'far in today's digital era, who explains knowledge that is easy to understand, stay healthy, Habib."